2018
DOI: 10.1037/vio0000090
|View full text |Cite
|
Sign up to set email alerts
|

Measuring acquired capability for suicide within an ideation-to-action framework.

Abstract: These findings implicate the PPEs that may be most important to assess in determining suicide risk, and, further, call into question the utility of acquired capability in differentiating between individuals along the suicide continuum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
28
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 73 publications
(119 reference statements)
4
28
1
2
Order By: Relevance
“…When individuals have high distress tolerance and “utilize coping methods that are sufficiently painful and/or provocative” (Law et al, , p. 31), such as fasting (Zuromski & Witte, ) and NSSI (Anestis et al, ; Anestis, Pennings, Lavender, Tull, & Gratz, ), their risk of progressing from ideation to suicidal behavior is pronounced. Indeed, frequent NSSI is empirically one of the strongest predictors of attempts (Burke et al, ; Hamza, Willoughby, & Good, ). Similarly, Burke et al () found that experiencing childhood abuse or neglect—which may habituate individuals to pain—significantly distinguished suicide attempters from ideators (see also Hadland et al, ; Rajalin, Hirvikoski, & Jokinen, ).…”
Section: The Role Of Emotion Dysregulation In Suicidementioning
confidence: 99%
See 3 more Smart Citations
“…When individuals have high distress tolerance and “utilize coping methods that are sufficiently painful and/or provocative” (Law et al, , p. 31), such as fasting (Zuromski & Witte, ) and NSSI (Anestis et al, ; Anestis, Pennings, Lavender, Tull, & Gratz, ), their risk of progressing from ideation to suicidal behavior is pronounced. Indeed, frequent NSSI is empirically one of the strongest predictors of attempts (Burke et al, ; Hamza, Willoughby, & Good, ). Similarly, Burke et al () found that experiencing childhood abuse or neglect—which may habituate individuals to pain—significantly distinguished suicide attempters from ideators (see also Hadland et al, ; Rajalin, Hirvikoski, & Jokinen, ).…”
Section: The Role Of Emotion Dysregulation In Suicidementioning
confidence: 99%
“…Indeed, frequent NSSI is empirically one of the strongest predictors of attempts (Burke et al, ; Hamza, Willoughby, & Good, ). Similarly, Burke et al () found that experiencing childhood abuse or neglect—which may habituate individuals to pain—significantly distinguished suicide attempters from ideators (see also Hadland et al, ; Rajalin, Hirvikoski, & Jokinen, ).…”
Section: The Role Of Emotion Dysregulation In Suicidementioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, acquired capability, characterized as habituation of fear and pain related to suicide (Van Orden et al., ), is considered a critical feature that may lead an individual to engage in high lethality suicidal behavior during acute high‐risk suicidal periods. Recently, Burke, Ammerman, Knorr, Alloy, and McCloskey () found people who reported an intent to die in a previous suicide attempt also endorsed a history of more painful and provocative events (e.g., nonsuicidal self‐injury) as compared to individuals with lower suicidal risk (e.g., suicidal ideation only). In the fluid vulnerability theory of suicidal behavior, the nonlinear patterns of suicide risk are emphasized, and repeated activation of a “suicidal mode” is thought to increase future risk by decreasing one's baseline threshold for suicidal behavior (Rudd, ).…”
mentioning
confidence: 99%